PERANCANGAN ILUSTRASI RETRO PADA SERAGAM T-SHIRT BRAND POLARISE SEBAGAI UPAYA PENGUATAN IDENTITAS VISUAL MEREK - Ismoyo, Katrin Nur Nafiah (AKSA: Jurnal Desain Komunikasi Visual, 2025)
This study discusses the design of retro-style illustrations for Polarise apparel as an effort to strengthen the brand’s visual identity. The background of this research stems from Polarise’s need to enhance its image and appeal through a distinctive and characterful visual approach. The design process adopts a qualitative method involving observation, visual analysis, illustration style exploration, and design experimentation. The retro style was chosen for its nostalgic aesthetic value and its ability to create an authentic impression of Polarise products such as knives and sharpening stones. The results show that the application of retro visual elements including warm color palettes, classic typography, and illustrative composition effectively reinforces the brand’s identity and provides differentiation within the tool-making industry.